Influence of concrete strength on dynamic interfacial fracture behaviour between fibre reinforced polymer sheets and concrete - Yuan, C.; Chen, Wensu; Pham, Thong; Hao, Hong; Cui, J.; Shi, Y. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This study experimentally investigates the effect of concrete strength on the dynamic interfacial bond behaviour between basalt fibre reinforced polymer (BFRP) sheets and concrete under different loading speeds (i.e. 8.33E−6 m/s, 0.1 m/s, 1 m/s, 3 m/s, 5 m/s, and 8 m/s) by using single-lap shear tests. Three concrete strengths (i.e. C20, C30, and C40) were considered to examine the influence of concrete strength and strain rate on the interfacial bond-slip responses under dynamic loadings. The test results including the strain distributions, interfacial fracture energy, and bond-slip response were evaluated and discussed. The test results showed that the BFRP-concrete interface exhibited sensitivity to strain rate and the bond strength and shear resistance of the interface enhanced with strain rate. Compared with high strength concrete, low strength concrete showed higher strain rate sensitivity, which is induced by the different interfacial fracture mechanisms under different strain rates. An empirical bond-slip model incorporating strength effect of concrete and strain rate was proposed based on fracture mechanics.